Correspondence. - Gaskell, Joshua; Partridge, Simon; Calder, Gideon; Fishel, Max; Hill, Barbara; McNair, Stephen; Joad, Derrick; Hodgson, Stuart; Davis, Mike; Charman-Blower, Sophie; Andrews, David; Ballard, Bob; et al. (New Statesman, 2014)
Letters to the editor are presented in response to articles in previous issues, including "Education's Berlin Wall" by David Kynaston and George Kynaston, "Health Matters" by Phil Whitaker, and "Squeezed Middle" by Alice O'Keeffe, all in the January 31, 2014, issue.